Plankton community as an indicator of water quality in tropical shrimp culture ponds. - Cunha, Maristela Casé Costa (2008)
The plankton was examined as an indicator of water quality in 14 shrimp Litopenaeus vannamei farms in Brazil in 2003. The ponds were categorized by high stocking density (>30 PL m_2) of phytoplankton, consisting of 51 species with concentrations ranging from 365,218 ± 416,615 cells mL_1 to 1,961,675 ± 3,160,172 cells mL_1. Diatoms contributed to almost 70% of the species number and high densities resulted from Cyanophyta blooms, mainly Pseudanabaena cf limnetica. Forty zooplankton taxa were registered and were essentially composed of typical marine euryhaline species and suspension-feeders. Copepoda dominated (45%) the make-up, followed by Protozoa (18%), Rotifera (12%), and Mollusca (12%) larvae. Zooplankton varied from 972 ± 209 ind m_3 to 4235 ± 2877 ind m_3. Enhanced nutrient input affected plankton density and composition. Diatom and Copepoda dominance was replaced by cyanobacteria, protozoan, and rotifers as nutrient concentrations increased with the cultured period, indicating that plankton structure is affected by eutrophic conditions.